2019
DOI: 10.1111/apa.15028
|View full text |Cite
|
Sign up to set email alerts
|

Tools to assess lung aeration in neonates with respiratory distress syndrome

Abstract: Aim Respiratory distress syndrome is a common condition among preterm neonates, and assessing lung aeration assists in diagnosing the disease and helping to guide and monitor treatment. We aimed to identify and analyse the tools available to assess lung aeration in neonates with respiratory distress syndrome. Methods A systematic review and narrative synthesis of studies published between January 1, 2004, and August 26, 2019, were performed using the OVID Medline, PubMed, Embase and Scopus databases. Results A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Recently, LUS has become an attractive new tool for assessing lungs in ventilated critically ill neonates. 1,13,23 Follow-up studies have shown that LUS has a more accurate diagnostic value than CXR in the detection of consolidations. The LUS helps in the differential diagnosis of RDS, interstitial syndrome, pleural effusions, pleural masses, consolidations, pneumothorax, and diaphragmatic dysfunction and provides procedural guidance for various pulmonary procedures such as thoracentesis, chest tube insertion, transthoracic aspiration, and biopsies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, LUS has become an attractive new tool for assessing lungs in ventilated critically ill neonates. 1,13,23 Follow-up studies have shown that LUS has a more accurate diagnostic value than CXR in the detection of consolidations. The LUS helps in the differential diagnosis of RDS, interstitial syndrome, pleural effusions, pleural masses, consolidations, pneumothorax, and diaphragmatic dysfunction and provides procedural guidance for various pulmonary procedures such as thoracentesis, chest tube insertion, transthoracic aspiration, and biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…The LUS helps in the differential diagnosis of RDS, interstitial syndrome, pleural effusions, pleural masses, consolidations, pneumothorax, and diaphragmatic dysfunction and provides procedural guidance for various pulmonary procedures such as thoracentesis, chest tube insertion, transthoracic aspiration, and biopsies. 23,24 In contrast to the adults, the lung structures of neonates, especially of preterm infants are immature. Preterm lungs are smaller, have thinner chest walls, and can be examined with fewer scans.…”
Section: Discussionmentioning
confidence: 99%
“…25 Followup studies showed that LU has a more accurate diagnostic value than CXRs. 26 A recent published review demonstrated LU has a shorter operation time than CXR, and a high concordance with CXR in the differential diagnosis of NRF, and confirms also the high level of accuracy for RDS, TTN, and pneumonia. 27 Another systematic review reported LU has a sensitivity and specificity of 97% and 91%, which were higher than clinical diagnosis and CXR results.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, LUSS requires the assessment of all lung surfaces (i.e., anterior, lateral and posterior) which could be difficult to obtain in critically ill neonates [27]. Notwithstanding, few studies sustained that LUSS had a better sensitivity with respect to the clinical score in pointing out children requiring surfactant replacement, particularly in preterm newborns of <30 weeks of gestational age [28,29]. Perri et al [30] demonstrated that LUSS could be used for the follow-up of newborns treated with surfactant replacement, monitoring the need for a second treatment after 2 h from the first administration.…”
Section: Lus In Neonatal Diseasesmentioning
confidence: 99%